2017
DOI: 10.1038/s41598-017-03356-x
|View full text |Cite
|
Sign up to set email alerts
|

Social odours covary with bacterial community in the anal secretions of wild meerkats

Abstract: The fermentation hypothesis for animal signalling posits that bacteria dwelling in an animal’s scent glands metabolize the glands’ primary products into odorous compounds used by the host to communicate with conspecifics. There is, however, little evidence of the predicted covariation between an animal’s olfactory cues and its glandular bacterial communities. Using gas chromatography-mass spectrometry, we first identified the volatile compounds present in ‘pure’ versus ‘mixed’ anal-gland secretions (‘paste’) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 71 publications
3
74
0
Order By: Relevance
“…Most social animals, however, communicate information (e.g., age, sex, physiological status) through scent, and a large part of the scent profile is attributable to skin bacteria (Kuhn & Natsch, ). Separate studies have documented distinct bacterial communities that appear to mediate the different chemical profiles in the scent glands of wild hyenas (Theis et al., ) and meerkats (Leclaire, Jacob, Greene, Dubay, & Drea, ).…”
Section: Microbiome Servicesmentioning
confidence: 99%
“…Most social animals, however, communicate information (e.g., age, sex, physiological status) through scent, and a large part of the scent profile is attributable to skin bacteria (Kuhn & Natsch, ). Separate studies have documented distinct bacterial communities that appear to mediate the different chemical profiles in the scent glands of wild hyenas (Theis et al., ) and meerkats (Leclaire, Jacob, Greene, Dubay, & Drea, ).…”
Section: Microbiome Servicesmentioning
confidence: 99%
“…MHC diversity has direct effects in combating diseases, and can therefore be reflected in various condition‐dependent traits (Dunn, Bollmer, Freeman‐Gallant, & Whittingham, ; Slade, Watson, & MacDougall‐Shackleton, ), including odour cues (Reusch, Haberli, Aeschlimann, & Milinski, ; Setchell et al, ; Thornhill et al, ). Similarly, in the context of the assessment of MHC dissimilarity to potential mates, most studies have shown the importance of odour cues (e.g., Leclaire, Strandh, Mardon, Westerdahl, & Bonadonna, ; Olsson et al, ; Ruff, Nelson, Kubinak, & Potts, ; Wedekind, Seebeck, Bettens, & Paepke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these results correspond to earlier findings on group‐specific meerkat scents, as meerkats were found to distinguish scent marks of intruders from those of group members (Mares et al., ). Furthermore, bacterial communities of adult meerkat scent secretions and social odours differed between groups, which was mainly attributed to group members sharing the same socio‐ecological environment (Leclaire et al., , ). Accordingly, our results also provide evidence that sampling with TD tubes is suitable for investigating biological questions on mammalian chemical communication.…”
Section: Discussionmentioning
confidence: 99%
“…Meerkats live in territorial groups comprising a dominant breeding pair and subordinate helpers related to the dominant pair at various degrees (Clutton‐Brock & Manser, ). They are known to discriminate between conspecific scents based on kinship (Leclaire, Nielsen, Thavarajah, Manser, & Clutton‐Brock, ) and group membership (Mares, Young, Levesque, Harrison, & Clutton‐Brock, ), and possess scent glands in an anal pouch, whose bacterial communities and corresponding odours vary with sex and group membership (Leclaire, Jacob, Greene, Dubay, & Drea, ; Leclaire, Nielsen, & Drea, ). These attributes, in combination with the relatively controlled captive setting, create an attractive system for investigating the use of TD tubes for non‐invasive sampling of mammalian body odour from both, a methodological and a biological perspective.…”
Section: Introductionmentioning
confidence: 99%